2003
DOI: 10.1152/jn.01033.2002
|View full text |Cite
|
Sign up to set email alerts
|

Amygdala Input Promotes Spread of Excitatory Neural Activity From Perirhinal Cortex to the Entorhinal–Hippocampal Circuit

Abstract: A number of sensory modalities most likely converge in the rat perirhinal cortex. The perirhinal cortex also interconnects with the amygdala, which plays an important role in various motivational and emotional behaviors. The neural pathway from the perirhinal cortex to the entorhinal cortex is considered one of the main paths into the entorhinal-hippocampal network, which has a crucial role in memory processes. To investigate the potential associative function of the perirhinal cortex with respect to sensory a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
72
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(87 citation statements)
references
References 46 publications
8
72
0
Order By: Relevance
“…The superficial ER layers receive input from PR and IT, and the duration of activity in superficial ER observed here is similar to that noted in these lateral areas. Furthermore, animal studies suggest that convergent and/or sustained activation may be necessary to evoke ER activity from PR and IT (Biella et al, 2002a), and that the presence of activity in deep layers of PR indicates that it has become sufficiently active to evoke an ER response (Kajiwara et al, 2003). In the current study, activity was simultaneously present in PR and IT, and the deep layers of PR showed strong sustained MUA, both suggesting that the lateral activation was sufficient to activate ER.…”
Section: Intracolumnar and Intercolumnar Circuitry Of Word Processingsupporting
confidence: 53%
“…The superficial ER layers receive input from PR and IT, and the duration of activity in superficial ER observed here is similar to that noted in these lateral areas. Furthermore, animal studies suggest that convergent and/or sustained activation may be necessary to evoke ER activity from PR and IT (Biella et al, 2002a), and that the presence of activity in deep layers of PR indicates that it has become sufficiently active to evoke an ER response (Kajiwara et al, 2003). In the current study, activity was simultaneously present in PR and IT, and the deep layers of PR showed strong sustained MUA, both suggesting that the lateral activation was sufficient to activate ER.…”
Section: Intracolumnar and Intercolumnar Circuitry Of Word Processingsupporting
confidence: 53%
“…This hypothesis is supported by electrophysiological evidence in vitro which shows that the perirhinal cortex does act as a gateway between the amygdala and the hippocampal-parahippocampal network (Koganezawa et al, 2008). Koganezawa et al (2008) also show using slices cut along a different axis to Kajiwara et al (2003) that stimulation of the lateral nucleus or of area 35 alone is enough to propagate information to the entorhinal cortex and dentate gyrus but that simultaneous stimulation of the lateral nucleus and area 36 was needed to elicit a response in the entorhinal cortex or the dentate gyrus. Further electrophysiological analysis of these projections is required to fully flesh out the hypothesis of the perirhinal cortex as an associative area for sensory and emotional information although we review the functional evidence for this hypothesis in Section 4.4.…”
Section: Subcortical Afferents and Efferents Of The Perirhinal Cortexmentioning
confidence: 75%
“…Moreover, while electrophysiological stimulation of either the lateral nucleus or the superficial perirhinal cortex in vitro does not propagate to the entorhinal cortex, simultaneous stimulation of the lateral nucleus and the superficial perirhinal cortex (which they use to approximate sensory input to the perirhinal cortex) results in strong depolarisation in the deep layers of area 35 and this electrophysiological response was propagated to the entorhinal cortex and dentate gyrus . Based on this evidence, Kajiwara et al (2003) posit that the perirhinal cortex acts as an association area for emotional and sensory information before these types of information enter the hippocampus. This hypothesis is supported by electrophysiological evidence in vitro which shows that the perirhinal cortex does act as a gateway between the amygdala and the hippocampal-parahippocampal network (Koganezawa et al, 2008).…”
Section: Subcortical Afferents and Efferents Of The Perirhinal Cortexmentioning
confidence: 99%
“…In the rat, the amygdala projects to ventral subiculum, parasubiculum and lateral entorhinal cortex (Krettek and Price, 1977). Furthermore, (Kajiwara et al, 2003) have shown that amygdalar stimulation promotes the spread of excitatory neural activity from perirhinal cortex to the entorhinal-hippocampal circuit (the hippocampal formation circuitry is extensively reviewed in (Schwartzkroin and McIntyre, 1997;Witter and Amaral, 2004)). Thus, electrical stimulation of the entorhinal cortex/perforant pathway, medial septum/septohippocampal pathway and the amygdala all stimulate the hippocampal trisynaptic excitatory circuit thought to be an important component of the kindling phenomenon Savage et al, 1985;Yoshida, 1984).…”
Section: Discussionmentioning
confidence: 99%